Architecture muséale : une figure de l’art de la ville "Du British Museum à la spirale du Victoria & Albert Museum à Londres" - Isabelle Alzieu (Anglophonia)
Beginning with "the Beaubourg effect", which was confirmed and greatly enhanced by the "Bilbao effect", hundreds of museums are now being built all over the world and are consecrated in an extreme media storm, from their very conception, to the point that the architectural object itself is a work of art, even taking precedence over the collections for which it was conceived, and is one of the first artistic objects to be taken into consideration in a town. In this great fascination for museums, we like to recognize the spirit of the Enlightenment, which sees the museum as something indispensable for any self-respecting city, a monument and/or an ornament, an instrument which gives value to the bourgeois city, the key edifice in many urbanistic programs. The new museum, above and beyond its economic importance, has become an essential element of symbolic capital for a city. This is true of the architectural object itself and the urbanistic project which accompanies it. Museal architecture, whether it be a contemporary creation or a rehabilitation, inevitably exhibits certain aesthetic norms which are revealed by the formal choices and the testimonies of the cultural attitudes of a given moment in time. The city prides itself on the multiplication of images offered by these places of art. Starting with an analysis of the architectural envelope of museums in the urban milieu, we will address the question of the museum as an ornament of the city. The demonstration will be developed using the city of London and its British Museum as a reference and will essentially refer to the projected extensions of the Victoria and Albert Museum and the Tate Modern.